Factors Associated With Medical and Nursing Students' Willingness to Donate Organs. Issue 12 (March 2016) - Tumin, Makmor; Tafran, Khaled; Tang, Li Yoong; Chong, Mei Chan; Mohd Jaafar, Noor Ismawati; Mohd Satar, NurulHuda; Abdullah, Nurhidayah
Abstract : Abstract: Malaysia suffers from a chronic shortage of human organs for transplantation. Medical and nursing students (MaNS) are future health professionals and thus their attitude toward organ donation is vital for driving national donation rates. This study investigates MaNS' willingness to donate organs upon death and the factors influencing their willingness. A cross-sectional design was used with a sample of 500 students (264 medical and 236 nursing) at the University of Malaya. A self-administrated questionnaire was used. The responses were analyzed by using descriptive statistics and multiple logistic regression. Of all respondents, 278 (55.6%) were willing to donate organs upon death, while the remaining 222 (44.4%) were unwilling to donate. Only 44 (8.8%) had donor cards. The multiple logistic regression revealed that the minorities ethnic group was more willing to donate organs than Malay respondents (adjusted odds ratio [aOR] = 1.98, P = 0.010). In addition, medical students were more willing to donate than nursing students (aOR = 2.53, P = 0.000). Respondents who have a family member with a donor card were more willing to donate than respondents who do not (aOR = 3.48, P = 0.006). MaNS who believed that their religion permits deceased donation were more willing to donate than their counterparts (aOR = 4.96, P = 0.000). Household income and sex were not significant predictors of MaNS' willingness to donate organs upon death. MaNS have moderate willingness, but low commitment toward deceased organ donation. Strategies for improving MaNS' attitude should better educate them on organ donation, targeting the most the Malay and nursing students, and should consider the influence of family attitude and religious permissibility on MaNS' willingness.